The anticipatory and consummatory interpersonal pleasure scale: Applicability to Chinese OCD patients - Lu, Jingjie; Wang, Xiang; Liu, Qian; Yu, Quanhao; Fan, Jie; Zhu, Xiongzhao (Frontiers in Psychology, 2023)
As a transdiagnostic symptom, social anhedonia has gained increasing attention. Evidence suggests that obsessive-compulsive disorder (OCD) patients demonstrate social anhedonia. This study examined the psychometric properties of the Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS) in an undergraduate sample and Chinese OCD patients. Furthermore, we explored the relationship between clinical symptoms and ACIPS scores. This study involved 3306 undergraduate students and 293 patients with OCD. Internal consistency and convergent validity of ACIPS were examined. Confirmatory factor analysis (CFA) was applied to determine the best-fitting of potential factor models, and multi-group CFA was used to examine measurement invariance across genders and samples. Additionally, hierarchical linear regression was conducted in order to investigate the relationship between clinical symptoms and ACIPS scores in patients suffering from OCD. ACIPS showed acceptable internal consistency in undergraduate and OCD samples (Cronbach’s α = 0.93 and 0.89, respectively). In both samples, the four-factor structure had the best fit index. Scalar invariance was established across undergraduate and OCD samples, while residual invariance was established across genders. In both samples, the ACIPS was significantly correlated with the Revised Social Anhedonia Scale and Beck Depression Inventory. Depression and the severity of obsessive thoughts significantly and negatively correlated with the ACIPS score in OCD patients (p <0.05). In conclusion, ACIPS is a reliable, effective, simple, and convenient tool for the assessment of social anhedonia. Depression and obsessive thoughts contribute to social anhedonia in OCD patients.